The structure and function of protein kinase C-related kinases (PRKs) - Sophocleous, Georgios (Biochem Soc Trans, 2021)
The protein kinase C-related kinase (PRK) family of serine/threonine kinases, PRK1, PRK2 and PRK3, are effectors for the Rho family small G proteins. An array of studies have linked these kinases to multiple signalling pathways and physiological roles, but while PRK1 is relatively well-characterized, the entire PRK family remains understudied. Here, we provide a holistic overview of the structure and function of PRKs and describe the molecular events that govern activation and autoregulation of catalytic activity, including phosphorylation, protein interactions and lipid binding. We begin with a structural description of the regulatory and catalytic domains, which facilitates the understanding of their regulation in molecular detail. We then examine their diverse physiological roles in cytoskeletal reorganization, cell adhesion, chromatin remodelling, androgen receptor signalling, cell cycle regulation, the immune response, glucose metabolism and development, highlighting isoform redundancy but also isoform specificity. Finally, we consider the involvement of PRKs in pathologies, including cancer, heart disease and bacterial infections. The abundance of PRK-driven pathologies suggests that these enzymes will be good therapeutic targets and we briefly report some of the progress to date.